Growth characteristics of Uranoscopus scaber Linnaeus 1758, inhabiting the Iskenderun Bay (Northeastern Mediterranean) - Basusta, Nuri; Ozmen, Mustafa M. (Wiley, 2020)
This study aimed to determine the age and some growth characteristics of Atlantic stargazer (Uranoscopus scaber) from Iskenderun Bay (Northeastern Mediterranean). For this purpose, a total of 150 Atlantic stargazer ranging in size from 9.1 to 28.0 cm in total length (weight: 11.7-345.7 g) were collected as by-catch from a commercial trawl fishing boat at a depth of 80-100 m between May 2015 and January 2016. The bottom trawl gear used was equipped with a 44 mm stretched mesh size net at the cod-end. The percentage of females and males were 46.7% and 53.3% respectively. The total length-weight relationships equation with coefficient of determination (R-2) were found as W = 0.011*TL3.131, R-2 = .9728, for all individuals, W = 0.015*TL3.021, R-2 = .9512 for females and W = 0.0102*TL3.136, R-2 = .9553 for males. By using the von Bertalanffy equation, the growth parameters of Atlantic stargazer were estimated to be L-infinity = 42.35 cm, k = 0.098, t(0) = -1.8474 for all individuals; L-infinity = 36.92 cm, k = 0.138, t(0) = -1.2693 for females and L-infinity = 38.77 cm, k = 0.1, t(0) = -2.334 for males. In this study, age reading was done by two independent readers and index of average percentage error (IAPE) was calculated as 6.1%. The highest condition factor value calculated as 1.81 in the age group 6 and the lowest condition factor value was calculated as 1.48 in the age group 1.
2nd International Fisheries Symposium (IFSC) -- NOV 04-08, 2018 -- Girne, CYPRUS
Keywords: Length-Weight Relationships; Aegean Sea; Fish; Age; Precision